Teachers’ Strategies to Overcome Students’ Difficulties in Learning English Vocabulary at Islamic Boarding School - Ainun Jariah Usman; Abdullah; Muhammad Tahir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to explore how teachers overcome students’ difficulties in learning English vocabulary at Pesantren Yapid At-Taubah by identifying students’ challenges, influencing factors, and the strategies used by the teacher. This research employed a qualitative method involving one English teacher and several students selected through purposive sampling. Data were collected through classroom observations and interviews and analyzed using data condensation, data display, and conclusion drawing. The findings reveal that students experience difficulties in pronunciation, word complexity, grammatical patterns, understanding meaning, and listening comprehension. These difficulties are influenced by internal factors such as low motivation and limited vocabulary mastery, as well as external factors such as teaching methods and limited exposure to English. To address these challenges, the teacher applied various strategies, including determination, social, memory strategies, cognitive, and metacognitive strategies, as well as vocabulary notebooks and Communicative Language Teaching (CLT). These strategies were found to be effective in helping students understand, retain, and use vocabulary more appropriately, thereby improving their vocabulary mastery and confidence.